KnowledgeBoat Logo

Mathematics

Given A is an acute angle and cosec A = 2\sqrt{2}, find the value of

2 sin2A+3 cot2Atan2Acos2A\dfrac{\text{2 sin}^2 A + 3\text{ cot}^2 A}{\text{tan}^2 A - \text{cos}^2 A}

Trigonometrical Ratios

45 Likes

Answer

Let triangle ABC be a right-angled at B and A is a acute angle.

Given A is an acute angle and cosec A = √2, find the value of (2 sin^2 A + 2 cot^2 A)/(tan^2 A - cos^2 A). Trigonometrical Ratios, ML Aggarwal Understanding Mathematics Solutions ICSE Class 9.

Given,

cosec A = 2\sqrt{2}

⇒ cosec A = HypotenusePerpendicular\dfrac{\text{Hypotenuse}}{\text{Perpendicular}}

= ACBC=21\dfrac{AC}{BC} = \dfrac{\sqrt{2}}{1}

Let AC = 2\sqrt{2}k and BC = k.

In right angled triangle ABC,

By using pythagoras theorem,

AC2 = AB2 + BC2

(2k\sqrt{2}k)2 = AB2 + k2

2k2 = AB2 + k2

AB2 = 2k2 - k2

AB2 = k2

AB = k\sqrt{\text{k}} = k.

By formula,

sin A = PerpendicularHypotenuse\dfrac{\text{Perpendicular}}{\text{Hypotenuse}}

= BCAC=k2k=12\dfrac{BC}{AC} = \dfrac{k}{\sqrt{2}k} = \dfrac{1}{\sqrt{2}}.

tan A = PerpendicularBase\dfrac{\text{Perpendicular}}{\text{Base}}

= BCAB=kk=1\dfrac{BC}{AB} = \dfrac{k}{k} = 1.

cot A = 1tan A=11=1\dfrac{1}{\text{tan A}} = \dfrac{1}{1} = 1.

cos A = BaseHypotenuse\dfrac{\text{Base}}{\text{Hypotenuse}}

= ABAC=k2k=12\dfrac{AB}{AC} = \dfrac{k}{\sqrt{2}k} = \dfrac{1}{\sqrt{2}}.

Substituting these values in 2 sin2A+3 cot2Atan2Acos2A\dfrac{\text{2 sin}^2 A + 3\text{ cot}^2 A}{\text{tan}^2 A - \text{cos}^2 A} we get,

2×(12)2+3×1212(12)22×12+3×11121+3124×28.\Rightarrow \dfrac{2 \times \Big(\dfrac{1}{\sqrt{2}}\Big)^2 + 3 \times 1^2}{1^2 - \Big(\dfrac{1}{\sqrt{2}}\Big)^2} \\[1em] \Rightarrow \dfrac{2 \times \dfrac{1}{2} + 3 \times 1}{1 - \dfrac{1}{2}} \\[1em] \Rightarrow \dfrac{1 + 3}{\dfrac{1}{2}} \\[1em] \Rightarrow 4 \times 2 \\[1em] \Rightarrow 8.

Hence, 2 sin2A+3 cot2Atan2Acos2A\dfrac{\text{2 sin}^2 A + 3\text{ cot}^2 A}{\text{tan}^2 A - \text{cos}^2 A} = 8.

Answered By

20 Likes


Related Questions